A device for studying fluid-induced cracks under mixed-mode loading conditions using x-ray tomography - Santarossa, Angel; Ortellado, Laureano; Sack, Achim; Gómez, Leopoldo R.; Pöschel, Thorsten (Review of Scientific Instruments, 2023)
We introduce an innovative instrument designed to investigate fluid-induced fractures under mixed loading conditions, including uniaxial tension and shear stress, in gels and similar soft materials. Equipped with sensors for measuring force, torque, and fluid pressure, the device is tailored for compatibility with x-ray tomography scanners, enabling non-invasive 3D analysis of crack geometries. To showcase its capabilities, we conducted a study examining crack-front segmentation in a hydrogel subjected to air pressure and a combination of tension and shear stress.
CRIS-Team Scopus Importer:2023-08-11